Galanin (1–15)-fluoxetine interaction in the novel object recognition test. Involvement of 5-HT1A receptors in the prefrontal cortex of the rats. (1st September 2019) - Flores-Burgess, Antonio; Millón, Carmelo; Gago, Belen; García-Durán, Laura; Cantero-García, Noelia; Coveñas, Rafael; Narváez, José Angel; Fuxe, Kjell; Santín, Luis; Díaz-Cabiale, Zaida
Abstract: Galanin (1-15) [GAL(1–15)] participates in mood regulation and depression. GAL(1–15) is also able to enhance the antidepressant effects induced by Fluoxetine (FLX) in the forced swimming test through interaction between GALR1-GALR2 and 5-HT1A receptors that induced changes in the binding characteristics and mRNA of the 5-HT1AR in the hippocampus. Since the medial prefrontal cortex (mPFC) is a core region for the interaction between emotional processing and cognition with a high density of 5-HT1AR and GALR1 and GALR2, we have analyzed the binding characteristics and mRNA levels of 5-HT1AR in the mPFC after GAL(1–15)-FLX administration in the rats. GAL(1–15) increased the Kd and the Bmax of the 5HT1AR agonist binding in the mPFC as well as the mRNA levels of 5-HT1AR in mPFC. Moreover, GAL(1–15) reversed the effects of memory impairment induced by FLX(10 mg/kg) in the Novel Object Recognition task. GALR2 was involved in these effects, since the specific GALR2 antagonist M871 blocked GAL(1–15) mediated actions at behavioral level. On the contrary GAL(1–15) did not reverse the effect of FLX in the Object Location Memory task. In conclusion, our results describe an interactions between GAL(1–15) and FLX in the mPFC involving interactions at the 5-HT1AR receptor level in the plasma membrane with changes at the transcriptional level with implications also at functional level. The GALR1-GALR2-5-HT1A heteroreceptor could be postulated to be used to reverse some of the adverse effects of FLX on memory processes. Highlights: GAL(1–15) reverses the impaired memory effects induced by Fluoxetine in the Novel Object Recognition. GAL(1–15)/FLX interactions modified the binding and 5-HT1AR mRNA levels in the medial prefrontal cortex. GAL(1–15)-Fluoxetine differentially interact in the dorsal hippocampus and in the prefrontal cortex.